INTEGRATING MOBILE APPS IN LANGUAGE EDUCATION: BENEFITS AND CHALLENGES - Temirova Malika Rustamovna (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract.  The  rapid  development  of  mobile  technology  has  transformed language education by providing learners with flexible, interactive, and personalized learning  opportunities.  Mobile  applications  (apps)  have  become  valuable  tools  for enhancing  vocabulary,  grammar,  pronunciation,  listening,  speaking,  reading,  and writing skills. Their accessibility and user-friendly interfaces allow students to engage in  language  learning  anytime  and  anywhere.  Despite  these  advantages,  integrating mobile  apps  into  language  education  also  presents  several  challenges,  including technological limitations, learner distraction, unequal access to digital devices, and concerns about educational quality. This article examines the benefits and challenges of using mobile applications in language education and provides recommendations for educators to maximize their effectiveness.